Emerging leadership : a study of leadership thinking and its implications for business leadership and practice in the 21st century - Plougmann, E. M. T. (Elizabeth Mary Therese) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2000.